2012
DOI: 10.5402/2012/145127
|View full text |Cite
|
Sign up to set email alerts
|

Moderate-Intensity Exercise Improves Body Composition and Improves Physiological Markers of Stress in HIV-Infected Men

Abstract: HIV/AIDS and its treatment often alter body composition and result in poorer physical functioning. The aim of this study was to determine the effects of a moderate-intensity exercise program on body composition and the hormones and cytokines associated with adverse health outcomes. HIV-infected males (N = 111) were randomized to an exercise group (EX) who completed 6 weeks of moderate-intensity exercise training, or to a nonintervention control group (CON). In pre- and postintervention, body composition was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 73 publications
4
39
0
1
Order By: Relevance
“…However, the anti-inflammatory effect of exercise in HIV infection has been rarely addressed in clinical studies. Reductions of hsCRP, IL-6, TNF-α and IL-18, a cytokine released by adipocytes and other cell types, were observed in a 16-week study of aerobic or resistance training performed at variable intensity [22], but no of IL-6 after 6 weeks of aerobic plus resistance moderate intensity exercise [27]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the anti-inflammatory effect of exercise in HIV infection has been rarely addressed in clinical studies. Reductions of hsCRP, IL-6, TNF-α and IL-18, a cytokine released by adipocytes and other cell types, were observed in a 16-week study of aerobic or resistance training performed at variable intensity [22], but no of IL-6 after 6 weeks of aerobic plus resistance moderate intensity exercise [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported testosterone [57,59], three studies free testosterone [5759] and two studies interleukin-6 and interleukin-1β [58,60]. All studies reported that samples were taken in a fasting state at the same time of day and in a rested state.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous prospective cohort studies have repeatedly shown that higher levels of physical activity are associated with reduced incidence of CVD, diabetes, certain cancers, all-cause mortality, and many other chronic conditions (Bassuk & Manson, 2005; Blair et al, 1996; Church et al, 2002; Jaggers et al, 2009; Warburton et al, 2006). Emerging data are showing similar benefits among HIV patients (Bopp et al, 2004; Dudgeon et al, 2012; Hand et al, 2008; Hand, Lyerly, Jaggers, & Dudgeon, 2009). However, no one has focused specifically on the components of MetSyn when studying the effects of physical activity among PLWHA.…”
Section: Introductionmentioning
confidence: 97%